Penerapan Pendekatan Kontekstual (CTL) Untuk Meningkatkan Hasil Belajar Mahasiswa Program Studi PGSD UNM Kampus Parepare Pada Mata Kuliah PKn I - Ritha Tuken; Yonathan Saba' Pasinggi (Publikasi Pendidikan, 2018)
This study aims to determine the application of the contextul approach (CTL) performed a lecturer in improving student learning outcomes in learning PKn1. This is done to determine the direction and policies in improving student learning outcomes On learning PKn1. This study uses kualitiatif approach, this type of research is action class research which is located in Prodi PGSD UNM Kampus Parepare. Site selection based on the consideration of researchers looked at the application of a contextual approach to teaching and learning (CTL) in a Civics course, the lecturers are still less able to be applied properly. The study procedures that (1) Planning, (2) Implementation, (3) observation, (4) reflection. Data collection techniques used in this study include (1) observation, (2) Documentation, (3) Interview, (4) tests. Data analysis is an effort to improve student learning outcomes with the application of a contextual approac. The results on initial tests showed that students' ability to understand the subject matter is still lacking in that category, after learning showed a significant increase with the evaluation results on the cycle I was on the qualifications sufficient (c), continued research on the cycle II because researchers have not puasdengan results obtained in cycle I, the evaluation results on the second cycle showed a significant increase in the category of very good results. This shows that the application of a contextual  approach  to  learning PKn1 can improve learning outcomes of students in Prodi PGSD UNM Kampus Parepare.